Academic Staffs Perception towards Female Students Affirmative Action in Higher Education: the Case of Wolaita Sodo University (Global Journal of Human-Social Science, 2016)
The major purpose of this study was to explore Academic Staff's Perceptions towards female students' affirmative action in Wolaita Sodo University. I employed case study method. The respondents were Academic staff, female students, gender coordinator and gender focal persons. The respondents were selected using purposive sampling technique. To collect the necessary data, face to face interviews, focus group discussion and document analysis were used. The result of the study indicates that in its current status, academic staff's perceptions towards female students' affirmative action were found varied. Thus, it can be argued from this study that academic staff perceptions concerning the definition and significance of female affirmative action were found positive where as their perception towards female student' support, gender friendly environment, access to various resources and department placement were found negative and inconsistent.
Keywords: affirmative action; academic staff; female students; perception; higher education